2017
DOI: 10.1162/coli_a_00276
|View full text |Cite
|
Sign up to set email alerts
|

Argumentation Mining in User-Generated Web Discourse

Abstract: The goal of argumentation mining, an evolving research field in computational linguistics, is to design methods capable of analyzing people's argumentation. In this article, we go beyond the state of the art in several ways. (i) We deal with actual Web data and take up the challenges given by the variety of registers, multiple domains, and unrestricted noisy user-generated Web discourse. (ii) We bridge the gap between normative argumentation theories and argumentation phenomena encountered in actual data by ad… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
181
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 199 publications
(184 citation statements)
references
References 128 publications
0
181
0
3
Order By: Relevance
“…Including comments opens many above-mentioned use cases. Natural language processing (NLP) technology can help to make sense out of this data, in particular, the field of argumentation mining (Habernal and Gurevych, 2017). Sentiment analysis, in its basic definition, reveals the polarity of the texts (positive, negative, neutral).…”
Section: Introductionmentioning
confidence: 99%
“…Including comments opens many above-mentioned use cases. Natural language processing (NLP) technology can help to make sense out of this data, in particular, the field of argumentation mining (Habernal and Gurevych, 2017). Sentiment analysis, in its basic definition, reveals the polarity of the texts (positive, negative, neutral).…”
Section: Introductionmentioning
confidence: 99%
“…An argumentative text is one that contains argumentation, i.e., a claim supported by evidence, and presented as a coherent whole. The extensive literature on argumentation has identified linguistics aspects that pinpoint to argumentative texts (Biber, 1988;van Eemeren et al, 2007;Moens et al, 2007;Tseronis, 2011;Habernal and Gurevych, 2017). Based on this research, we include argumentation lexical cues, such as discourse connectives and stance adverbials, in our set of features.…”
Section: Svms With Constructiveness Featuresmentioning
confidence: 99%
“…However, if the documents are sufficiently long, argumentative structure could in principle be recovered. In a recent study on social media texts, Habernal and Gurevych (2016) showed that (a slightly modified) Toulmin's argumentation model may be suitable for short documents, such as article comments or forum posts. Using sequence labeling, they identify the claim, premise, backing, rebuttal, and refutation components, achieving a token-level F1-score of 0.25.…”
Section: Related Workmentioning
confidence: 99%